2023
DOI: 10.3390/electronics12204289
|View full text |Cite
|
Sign up to set email alerts
|

IoT Intrusion Detection System Based on Machine Learning

Bayi Xu,
Lei Sun,
Xiuqing Mao
et al.

Abstract: With the rapid development of the Internet of Things (IoT), the number of IoT devices is increasing dramatically, making it increasingly important to identify intrusions on these devices. Researchers are using machine learning techniques to design effective intrusion detection systems. In this study, we propose a novel intrusion detection system that efficiently detects network anomalous traffic. To reduce the feature dimensions of the data, we employ the binary grey wolf optimizer (BGWO) heuristic algorithm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Comparing our suggested methodology with current state-of-the-art methods allowed for a thorough assessment of its effectiveness, provided in Tables 4-6. In particular, our method was thoroughly tested against prominent techniques [14,17,18]. This thorough comparison study sought to clarify our suggested approach's unique benefits and functional characteristics with these state-of-the-art works.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparing our suggested methodology with current state-of-the-art methods allowed for a thorough assessment of its effectiveness, provided in Tables 4-6. In particular, our method was thoroughly tested against prominent techniques [14,17,18]. This thorough comparison study sought to clarify our suggested approach's unique benefits and functional characteristics with these state-of-the-art works.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al [17] employed the binary grey wolf optimizer (BGWO) heuristic algorithm and recursive feature elimination (RFE) to select features for their intrusion detection system. They used the synthetic minority oversampling technique (SMOTE) to oversample the minority classes.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Authors in [23], proposed a CorrAUC that uses a feature selection metric and an algorithm to filter features accurately. The procedure is assessed using the dataset of the Bot-IoT and four different machine learning methods, the average accuracy of which is over 96%.In [24], authors proposed a method of intrusion detection for IoT devices that utilizes machine learning to identify anomalous traffic in the network. The system uses binary grey wolf optimizer, recursive feature elimination, synthetic minority oversampling technique, XGBoost, Bayesian, and classification optimization with a tree-structured Parzen estimator.…”
Section: Related Workmentioning
confidence: 99%